Analisis Manajemen Keuangan di UPT Sekolah Dasar Negeri 234 Gresik - Alvian, Aqilla Rizki; Farihah, Azza Atiqotul Maula Al; Wulandari, Ayu; Abida, Innafi Hamda; Damayanti, Sofia Dwi; Latifah, Ummi; Nuphanudin, Nuphanudin (ARZUSIN, 2024)
This research discusses financial management at UPT SDN 234 Gresik, to extract funds, manage School Operational Assistance (BOS) funds, make reports and financial accountability, and conduct supervision. This study used a qualitative descriptive method. Primary data was obtained through interviews with school treasurers, and additional data from literature studies. Thus, the focus of this research is on the financial management aspect of the school. The research results show that this educational institution implements financial principles involving fairness, efficiency, transparency, and public accountability in managing its financial resources. The school's funding cycle includes steps such as sourcing funds, planning, supervision, and financial reporting. The use of the ARKAS application helps improve transparency and efficiency, although there are still challenges related to reliance on a stable internet connection. This research provides valuable insights for stakeholders in the world of education, efforts to improve the quality of education in the school environment are important.